2020
DOI: 10.1186/s12887-020-02413-1
|View full text |Cite
|
Sign up to set email alerts
|

Bullying victimization among Lebanese adolescents: The role of child abuse, Internet addiction, social phobia and depression and validation of the Illinois Bully Scale

Abstract: Background Both bullying victimization and perpetration were associated with depression, social phobia, physical and psychological child abuse and Internet addiction in Lebanon. The prevalence of bullying in Lebanon is alarming, with 50% of school-aged children and adolescents reporting being bullied at some point. The high rate of both bullying victimization can be reflective of the inefficacy of current prevention and intervention policies in targeting associated problematic individual and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 87 publications
3
38
0
Order By: Relevance
“…Excluded were students that declined to fill the survey. This paper shares the same methodology as other papers from the same project [22][23][24][25][26][27].…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…Excluded were students that declined to fill the survey. This paper shares the same methodology as other papers from the same project [22][23][24][25][26][27].…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…This scale, validated in Lebanon [ 46 ], is used to measure bullying perpetration and victimization through a direct survey. The bullying victimization subscale was only considered in this study.…”
Section: Methodsmentioning
confidence: 99%
“…This scale, validated in Lebanese adolescents [ 39 ], was constructed by the World Health Organization (WHO) [ 40 ] with the purpose of profiling alcohol consumption, drinking patterns and drinking related problems. Due to the nature of this study, a self-reported version of this scale was administered, with a score of 8 or more pointing towards the presence of alcohol use disorder.…”
Section: Methodsmentioning
confidence: 99%